Telenursing as an Effective Ally for Improving Patient Outcomes in Diabetes? An Umbrella Review - Marika Lo Monaco; Arianna Profeta; Salvatore Corrao (Nursing Open, 2025)
ABSTRACT Aim To evaluate telenursing interventions' effectiveness in managing patients with diabetes mellitus. Design Overview of systematic reviews. Review Methods According to the PRISMA statement, we included studies published from 2005 to 2023 that evaluated telenursing interventions for adult diabetic patients and reported physiological, behavioural, and clinical outcomes. AMSTAR 2 was used to assess the quality of the included studies. Data Sources We conducted an umbrella review from July 2023 to May 2024, searching Cochrane Library, PubMed, SCOPUS, and PROSPERO for systematic reviews published from inception to May 10, 2024. Results Thirty‐one eligible systematic reviews were identified. Most (n = 23) reported positive effects of telenursing interventions (telephone calls, text messaging, mobile software applications, telecoaching) on reducing glycated haemoglobin (HbA1c). Findings on weight loss, hypoglycaemia, and quality of life were heterogeneous. Telenursing interventions promoted self‐management behaviours like medication adherence and dietary improvements. While several studies suggested potential cost‐effectiveness, further studies are needed to explore the long‐term economic impact of telenursing on diabetes management. Conclusions Telenursing appears to be a promising approach for improving diabetes management, particularly in self‐management behaviours and HbA1c control. Further research is needed to explore the long‐term sustainability, cost‐effectiveness, and optimal telenursing protocols for diabetes care. Implication for the Profession and/or Patient Care This umbrella review highlights the significant role of telenursing in improving diabetes management and patient outcomes. Nurse‐led telehealth interventions have demonstrated their ability to enhance patient self‐management, adherence to treatment plans, and overall well‐being. Additionally, by reducing hospitalisations and healthcare costs and increasing access to care for patients living in rural areas, nurse‐led telehealth interventions represent an effective strategy for improving diabetes care despite initial costs. Given these findings, healthcare providers and policymakers should implement telenursing programs to enhance patient care and system efficiency. Reporting Method The authors adhered to the EQUATOR guidelines using the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) and “the Preferred Reporting Items for Overviews of Reviews Statement” (PRIOR) for the reporting. Patient or Public Contribution There was no patient contribution. The European Union—ERDF or ESF, OP Research and Innovation 2014–2020—DM 1062/2021 co‐financed the publication. Trial Registration International Prospective Register of Systematic Reviews (PROSPERO) with the protocol number CRD42023427103 https://www.crd.york.ac.uk/PROSPEROFILES/427103_STRATEGY_20230719.pdf